Penyusunan Pedoman Atas Pemasukkan Dan Pengeluaran Kas Pada Pesantren Baitul’ulum Wal Huffadz Al Usmani - Aulia, Chika; Khairunnisa , Hera; Anggraini, Ratna (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the preparation of guidelines for cash income and expenditure at the Baitul'ulum Wal Huffadz Al Usmani Islamic Boarding School. This research design uses a research and development approach (R&D) with the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation. The ADDIE model serves as a reference in designing accounting guidelines, SOPs, and documents for an effective, efficient, and structured cash income and expenditure cycle. Based on the results of the study, it was found that the process of managing cash income and expenditure at the Baitul'ulum Wal Huffadz Al Usmani Islamic Boarding School is still carried out simply. Financial records are managed by the Islamic boarding school treasurer with a prior approval mechanism from the Islamic boarding school leadership. However, these records are not yet supported by written guidelines and standard procedures, so cash management still depends on the habits and understanding of financial managers. This study resulted in a draft of cash income and expenditure guidelines compiled based on the results of interviews, observations, and the actual needs of the Islamic boarding school. These guidelines include the preparation of supporting documents, a procedural flow for cash receipts and disbursements, and examples of simple record keeping, which are expected to assist Islamic boarding schools in realizing more orderly, transparent, and accountable financial management.